A method for producing anti-thermal oxidation degradation functional antimony-free polyester fiber

By combining small phosphate molecules with inorganic powders, nanopowders with anti-thermal oxygen degradation are prepared, which solves the problem of thermal oxygen degradation in polyester fibers during processing, and achieves the efficient thermal oxygen resistance of antimony-free polyester fibers and stability, suitable for a variety of application scenarios.

CN115976685BActive Publication Date: 2024-12-27SHANGHAI HUIYI NEW MATERIALS TECH CO LTD +2
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202111203338.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-15
Publication Date
2024-12-27
Estimated Expiration
2041-10-15

AI Technical Summary

Technical Problem

Existing polyester fibers are prone to thermal oxygen degradation during processing, resulting in a decrease in the inherent viscosity and viscoelasticity. The dispersion of nanomaterials in high-temperature and high-pressure environments is poor, affecting the stability of thermal oxygen resistance.

Method used

The phosphate-like small molecules are combined with inorganic powders, and the insoluble salts are formed through van der Waals force, hydrogen bonds or covalent bonds, and the inorganic powders are deposited or coated to prepare phosphate-modified anti-thermal oxygen degradation function nanopowders, and It is introduced into antimony-free polyester, and a thermal oxygen-resistant functional antimony-free polyester fiber is produced by copolymerization or blending of spinning.

Benefits of technology

The anti-thermal oxygen degradation performance of anti-anti-free polyester is significantly improved, and the thermal oxygen degradation is inhibited, and the efficient dispersion and stability of antimony-free polyester fiber is achieved, which improves the spinning performance and use performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a method for manufacturing a functional antimony-free polyester fiber resistant to thermal oxidation degradation. After introducing a phosphate-modified anti-thermal oxidation degradation functional nano powder into an antimony-free polyester to obtain a functional antimony-free polyester, the functional antimony-free polyester is spun as part or all of a raw material to obtain a functional antimony-free polyester fiber resistant to thermal oxidation degradation. The phosphate-modified anti-thermal oxidation degradation functional nano powder is an inorganic powder with a phosphate-type small molecule having a thermal oxidation degradation resistance function deposited or coated on the surface. The phosphate-type small molecule is bound to the inorganic powder by van der Waals force, hydrogen bond or covalent bond. The phosphate-type small molecule is a phosphate-type molecule with a molecular weight of less than 500 Da. Compared with a comparative sample, the initial decomposition temperature of the functional antimony-free polyester is increased by 14-15° C., and the maximum thermal weight loss temperature is increased by 10-12° C. The functional antimony-free polyester fiber prepared by the method of the invention has the advantages of good strength and washing resistance, and has the excellent processing performance and use performance of ordinary synthetic fibers, and does not contain heavy metal antimony harmful to the human body, and has a wide range of applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional polyester fibers and relates to a method for manufacturing functional antimony-free polyester fibers that are resistant to thermal oxidation degradation. Background Art

[0002] Polyester fiber, made from polyethylene terephthalate (PET), is traded as terylene in China. It is currently the leading synthetic fiber. Polyester fiber is an ideal textile raw material due to its high molecular chain rigidity and elastic modulus, making it resistant to deformation. Fabrics made from it remain wrinkle-free after washing, can be ironed, remain durable, and are easy to wash and dry. It also offers excellent heat, sunlight, and abrasion resistance, and can be used within temperatures ranging from -70°C to 170°C. Polyester fiber has a wide range of applications in apparel, home textiles, and industrial applications. However, its performance and functionality still fall short of consumer expectations.

[0003] Currently, antimony compounds are widely used as catalysts in the industrial production of polyethylene terephthalate (PET). Antimony-based catalysts are mature and inexpensive, but heavy metal antimony can remain in the polymer and pollute downstream printing and dyeing processes. Currently, the production of PET using titanium-based catalysts is becoming more stable and mature. However, the spinning process has a long thermal history and high processing temperatures (270-295°C). Heat and shear easily cause thermal and thermal oxidant degradation of the titanium-based catalyst-based PET, resulting in decreased intrinsic viscosity and viscoelasticity, increased end carboxyl group content, and the formation of large amounts of low-molecular-weight aldehydes. To prevent thermal oxidative degradation of PET during spinning, further enhance its melt viscoelasticity, and improve its spinning performance, antioxidants and heat stabilizers can be added during the spinning process. Chinese patent CN101545152A reports an aging-resistant high-strength nylon filament suitable for outdoor use and its preparation method, by adding phosphites and the like as anti-thermal oxidative degradation materials. However, small-molecule phosphites are not easy to exist stably in high-temperature and high-pressure polymer systems, are prone to migration, and are unevenly dispersed, affecting the stability of the composite material's anti-thermal oxidative performance.

[0004] Nanomaterials refer to materials whose dispersed phases have at least one dimension in the nanoscale range in three-dimensional space. They have excellent special effects, a large specific surface area, many interaction points with polymers, and a macroscopic quantum tunneling effect, resulting in good modification effects. Adding a small amount of nanomaterials to polymer fiber materials can achieve good functional effects and also enhance both reinforcement and toughness. Chinese patent CN18004514A reports an antibacterial PET fiber and a method for its preparation. The antibacterial function is imparted to the polyester matrix by adding nano zinc oxide, but this only imparts a single antibacterial function to the polyester fiber, and the dispersibility of inorganic materials in polymer materials is a major challenge. Chinese patent CN112281225A reports a method for preparing UV-resistant and flame-retardant polyester filaments. Nano titanium dioxide, silicon dioxide, and antimony trioxide are added to masterbatches to prepare polyester filaments with both UV-resistant and flame-retardant properties.

[0005] Therefore, it is of great significance to study an antimony-free polyester fiber with good thermal and oxygen resistance stability and good dispersion of functional nanomaterials. Summary of the Invention

[0006] The present invention aims to address the problems existing in the prior art and provide a method for manufacturing functional antimony-free polyester fibers that are resistant to thermal oxidative degradation. Specifically, the present invention utilizes the property that the hydrophilic phosphate groups of phosphate ester small molecules can form insoluble salts with metal ions and deposit or coat the surface of inorganic powders. This method anchors the phosphate ester small molecules to the inorganic powders, thereby modifying the inorganic powders. Due to the binding with the inorganic powders, the phosphate ester small molecules are less likely to migrate, and due to the binding with the phosphate ester small molecules, the inorganic powders can be well dispersed within the polymer matrix. Furthermore, using the environmentally friendly antimony-free polyester as the matrix and the modified inorganic powder as an additive, a new generation of antimony-free functional polyester fiber composite materials that are both resistant to thermal oxidative degradation and possess nanomaterial functionality are prepared, simultaneously solving both of these problems.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] A method for producing antimony-free polyester fibers with thermal-oxidative degradation resistance comprises introducing phosphate-modified anti-thermal-oxidative-degradation functional nanopowder (the specific introduction method is not limited; any method that can introduce phosphate-modified anti-thermal-oxidative-degradation functional nanopowder into antimony-free polyester is applicable to the present invention) into antimony-free polyester (i.e., polyester that does not contain antimony; the present invention uses titanium-based catalyst-based antimony-free polyester, i.e., polyester produced using a titanium-based catalyst) to produce the functional antimony-free polyester, which is then used as part or all of the raw material (when the content of the phosphate-modified anti-thermal-oxidative-degradation functional nanopowder in the functional antimony-free polyester is low, the phosphate-modified anti-thermal-oxidative-degradation functional nanopowder can be used as all of the raw material for spinning; when the content of the phosphate-modified anti-thermal-oxidative-degradation functional nanopowder in the functional antimony-free polyester is high, the phosphate-modified anti-thermal-oxidative-degradation functional nanopowder can be used as part of the raw material for spinning and co-spinned with the antimony-free polyester) to produce the antimony-free polyester fibers with thermal-oxidative-degradation resistance.

[0009] The phosphate-modified nanopowder with thermal-oxidative degradation resistance is an inorganic powder with phosphate-type small molecules deposited or coated on its surface with thermal-oxidative degradation resistance. The phosphate-type small molecules are bonded to the inorganic powder via van der Waals forces, hydrogen bonds, or covalent bonds. The phosphate-type small molecules have a molecular weight of less than 500 Da. In the present invention, since the phosphate-type small molecules are relatively small in volume compared to the submicron-level inorganic powder, after bonding with the inorganic powder, the phosphate-type small molecules are anchored to the inorganic powder and are less likely to migrate within the polymer matrix. Torque rheometer testing shows that the maximum torque of antimony-free polyester increases by 92% after adding the phosphate-modified nanopowder with thermal-oxidative degradation resistance, indicating that thermal-oxidative degradation is effectively inhibited.

[0010] As the preferred technical solution:

[0011] In the aforementioned method for producing antimony-free polyester fibers with thermal-oxidative degradation resistance, the phosphate ester small molecule with thermal-oxidative degradation resistance is one or more of triethyl phosphate, phosphoric acid, triphenyl phosphate, trimethyl phosphate, and triphenyl phosphite. The primary mechanism of action of the thermal-oxidative degradation-resistant phosphate ester small molecule is that it reacts with metal oxides that promote thermal degradation to form metal phosphate compounds, thereby inhibiting the metal oxide's activity against thermal-oxidative degradation. Furthermore, the phosphate ester is a decomposing agent for hydrogen peroxide produced during thermal-oxidative degradation. The phosphorus atom forms three PO atoms with three oxygen atoms attached to a benzene ring. The electron cloud surrounding the phosphorus atom is heavily biased toward the oxygen atom. Because the phosphorus atom has a lone pair of electrons, it readily forms a relatively stable compound with the oxygen atom of the unstable peroxide, interrupting the peroxide's decomposition into active free radicals and thereby preventing the occurrence of a chain reaction.

[0012] In the aforementioned method for producing functional antimony-free polyester fibers resistant to thermal and oxidative degradation, the inorganic powder is one or more of titanium dioxide, zinc oxide, cuprous oxide, ferric oxide, and silicon dioxide. Adding these inorganic powders to the fiber matrix can impart various functionalities, such as titanium dioxide imparting UV resistance, zinc oxide imparting antibacterial and deodorizing properties, cuprous oxide imparting high-performance antimicrobial properties, ferric oxide imparting microwave absorption, and silicon dioxide imparting reinforcement and whitening properties.

[0013] In the aforementioned method for producing a functional antimony-free polyester fiber resistant to thermal oxidative degradation, the average particle size of the inorganic powder is 0.4 to 0.8 μm. If the average particle size of the inorganic powder is too small, even a few times larger than the mean square radius of gyration of the phosphate ester small molecules, the inorganic powder will be pulled by the phosphate ester small molecules and will not be able to anchor the phosphate ester small molecules. If the average particle size of the inorganic powder is too large, uniform dispersion will be greatly increased.

[0014] The method for manufacturing a functional antimony-free polyester fiber with thermal-oxidative degradation resistance as described above comprises the following steps: dispersing an inorganic powder in a solvent (anhydrous ethanol), adding a phosphate ester small molecule having thermal-oxidative degradation resistance thereto at a temperature of 50 to 90° C., adjusting the pH value of the system to 4 to 5, maintaining the temperature, cooling, refluxing, and stirring the reaction for 30 to 90 minutes, and then cooling to room temperature. The system is then filtered, washed, and dried to obtain the phosphate ester modified thermal-oxidative degradation resistance nanopowder; the content of the inorganic powder in the system is 1 to 5% by weight, and the content of the phosphate ester small molecule having thermal-oxidative degradation resistance is 1 to 6% by weight.

[0015] The method for manufacturing a functional antimony-free polyester fiber resistant to thermal oxidation degradation as described above comprises the following steps: before introduction, phosphate-modified anti-thermal oxidation degradation functional nanopowder and polyethylene wax (polyethylene wax can be used as an anti-sticking agent and lubricant when blending polymer materials) are stirred in a closed mixer at a temperature of 60 to 70°C for 45 to 60 minutes in a weight ratio of 6 to 10:1.5 to 2 to obtain an anti-thermal oxidation degradation composite nanoagent.

[0016] The method for manufacturing a functional antimony-free polyester fiber resistant to thermal oxidation degradation as described above comprises the following steps: firstly, mixing an anti-thermal oxidation degradation composite nano-agent, sodium hexametaphosphate, and ethylene glycol in a weight ratio of 4 to 8:0.1 to 0.5:3 to 5, ultrasonically dispersing the mixture at a temperature of 50 to 60° C. for 2 to 3 hours to obtain functionalized ethylene glycol; then, when the esterification rate of polyethylene terephthalate (PET) reaches 85 to 90% (a titanium-based catalyst is used as the catalyst for PET polymerization), adding the functionalized ethylene glycol to the mixture, and continuing the esterification reaction and polycondensation reaction to obtain the functional antimony-free polyester; wherein the weight ratio of the functionalized ethylene glycol to terephthalic acid (one of the reaction raw materials of PET) is 35:65.

[0017] The aforementioned method for producing functional antimony-free polyester fibers resistant to thermal and oxidative degradation involves melt-blending an anti-thermal and oxidative degradation composite nano-agent with antimony-free polyester in a weight ratio of 20:80 to 40:60 to produce the functional antimony-free polyester. Due to the poor compatibility between inorganic powders and the polyester matrix, adding too much of the anti-thermal and oxidative degradation composite nano-agent complicates the preparation process and significantly impacts the spinning process upon subsequent addition. However, adding too little of the anti-thermal and oxidative degradation composite nano-agent results in poor technical and economic efficiency.

[0018] The method for manufacturing a functional antimony-free polyester fiber resistant to thermal oxidation degradation as described above comprises the following steps: mixing a functional antimony-free polyester with an antimony-free polyester to obtain a mixture, and then melt-spinning the mixture to obtain the functional antimony-free polyester fiber resistant to thermal oxidation degradation, wherein the content of the phosphate-modified anti-thermal oxidation degradation functional nanopowder in the functional antimony-free polyester fiber resistant to thermal oxidation degradation is 1.5 to 3.5 wt % (if the content is too low, it is difficult to exert the effect of the inorganic powder; if the content is too high, it will have a greater impact on the spinning production process).

[0019] According to the method for manufacturing a functional antimony-free polyester fiber resistant to thermal oxidative degradation as described above, the initial decomposition temperature of the functional antimony-free polyester is increased by 14 to 15°C, and the maximum thermal weight loss temperature is increased by 10 to 12°C compared to a control sample. The only difference between the control sample and the functional antimony-free polyester is that the control sample does not contain phosphate-modified anti-thermal oxidative degradation functional nanopowder. Therefore, it can be seen that the thermal oxidative degradation resistance of the antimony-free polyester is significantly improved after the addition of phosphate-modified anti-thermal oxidative degradation functional nanopowder. This also indirectly reflects that the phosphate small molecules in the phosphate-modified anti-thermal oxidative degradation functional nanopowder are not easy to migrate, because if the phosphate small molecules are easy to migrate, the thermal oxidative degradation resistance of the functional antimony-free polyester will deteriorate. The inorganic powder in the functional antimony-free polyester of the present invention can be evenly dispersed, and it can be seen from the SEM image that it is evenly dispersed without agglomeration.

[0020] The mechanism of the present invention is as follows:

[0021] Phosphate ester small molecules are amphiphilic. After the hydrophilic end binds to the metal ion, the hydrophobic end is arranged outward, thus forming an insoluble salt. The present invention utilizes the property that the phosphate group at the hydrophilic end of the phosphate ester small molecule can form an insoluble salt with the metal ion and be deposited or coated on the surface of the inorganic powder. The phosphate ester small molecules are anchored together with the inorganic powder, thereby achieving modification of the inorganic powder. Due to the binding with the inorganic powder, the phosphate ester small molecules are not easy to migrate. Due to the binding with the phosphate ester small molecules, the inorganic powder can be better dispersed in the polymer matrix. Then, using the environmentally friendly antimony-free polyester as the matrix and the modified inorganic powder as the additive, a new generation of antimony-free functional polyester fiber composite material that is both resistant to thermal oxidative degradation and has the function of a nanomaterial is prepared.

[0022] Beneficial effects

[0023] (1) The present invention provides a method for producing a thermal-oxidative-resistant antimony-free polyester fiber, wherein an inorganic powder and a phosphate ester small molecule having a thermal-oxidative-resistant function are prepared into a phosphate-modified thermal-oxidative-resistant nanopowder. This method anchors the phosphate ester small molecule on the inorganic powder, making it difficult for the phosphate ester small molecule to migrate within the polymer matrix.

[0024] (2) The present invention provides a method for producing a functional antimony-free polyester fiber resistant to thermal oxidation degradation, wherein a phosphate-modified nanopowder resistant to thermal oxidation degradation and an antimony-free polyester are copolymerized or blended and then melt-spun to produce the functional antimony-free polyester fiber. The method is simple and has wide adaptability.

[0025] (3) The functional antimony-free polyester fiber produced by the method for producing a functional antimony-free polyester fiber resistant to thermal oxidation degradation of the present invention has the advantages of good strength and washing resistance, and has the excellent processing performance and use performance of ordinary synthetic fibers, and does not contain heavy metal antimony that is harmful to the human body; it can be widely used in clothing, carpets, curtains, bedding, car seat cushions and hospitals, etc. DETAILED DESCRIPTION

[0026] Below in conjunction with specific embodiment, further set forth the present invention.Should be understood that these embodiments are only used to illustrate the present invention and are not used in limiting the scope of the present invention.In addition, should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall equally within the scope limited by the appended claims of the application.

[0027] The mechanical property test of the fiber of the present invention is carried out on a multifilament strength tester with a clamping distance of 250 mm, a pre-tension of 50 cN, and a stretching rate of 500 mm / min.

[0028] Example 1

[0029] A method for producing a functional antimony-free polyester fiber resistant to thermal oxidation degradation, comprising the following steps:

[0030] (1) Preparation of phosphate-modified functional nanopowders resistant to thermal oxidation degradation;

[0031] An inorganic powder (titanium dioxide) having an average particle size of 0.4 μm is dispersed in a solvent (anhydrous ethanol), and a phosphate ester small molecule having a thermal oxidative degradation resistance function (triethyl phosphate) is added thereto at a temperature of 50° C. The pH value of the system is adjusted to 4, and the mixture is kept warm, cooled, refluxed, and stirred for 30 minutes before being cooled to room temperature. The mixture is then filtered, washed (twice with anhydrous ethanol and twice with deionized water), and dried (110° C. for 10 hours) to obtain a phosphate-modified nanopowder having a thermal oxidative degradation resistance function; the content of the inorganic powder in the system is 1.5 wt %, and the content of the phosphate ester small molecule having a thermal oxidative degradation resistance function is 1 wt %;

[0032] The prepared phosphate-modified nanopowder with thermal-oxidative degradation resistance is an inorganic powder with phosphate-type small molecules deposited or coated on the surface, which has thermal-oxidative degradation resistance. The phosphate-type small molecules and the inorganic powder are bonded by van der Waals forces, hydrogen bonds or covalent bonds.

[0033] (2) Preparation of composite nanoagents resistant to thermal and oxidative degradation;

[0034] The phosphate modified anti-thermal oxidation degradation functional nano powder prepared in step (1) and polyethylene wax were stirred in a closed mixer at a temperature of 60° C. for 60 minutes to prepare an anti-thermal oxidation degradation composite nano agent in a weight ratio of 6:1.5;

[0035] (3) Preparation of functional antimony-free polyester;

[0036] The anti-thermal oxidative degradation composite nano-agent obtained in step (2), sodium hexametaphosphate and ethylene glycol are mixed in a weight ratio of 4:0.1:3, and ultrasonically dispersed at a temperature of 50°C for 2h to obtain functionalized ethylene glycol. When the esterification rate of polyethylene terephthalate polymerization reaches 85% (the catalyst used in the polymerization of polyethylene terephthalate is a titanium-based catalyst), the functionalized ethylene glycol is added thereto, and esterification reaction and polycondensation reaction are continued to obtain a functional antimony-free polyester, wherein the weight ratio of functionalized ethylene glycol to terephthalic acid is 35:65;

[0037] Compared with the control sample (the only difference between the control sample and the functional antimony-free polyester is that it does not contain phosphate-modified anti-thermal oxidation degradation functional nanopowder), the initial decomposition temperature of the prepared functional antimony-free polyester increased by 15°C and the maximum thermal weight loss temperature increased by 12°C.

[0038] (4) Preparation of anti-thermal oxidative degradation functional antimony-free polyester fiber;

[0039] Functional antimony-free polyester and antimony-free polyester (polyester produced using a titanium-based catalyst) are mixed to obtain a mixture, which is then melt-spun into a composite fiber to produce a functional antimony-free polyester fiber resistant to thermal oxidation degradation, wherein the content of the phosphate-modified anti-thermal oxidation degradation functional nanopowder in the functional antimony-free polyester fiber is 1.5 wt%.

[0040] The prepared anti-thermal oxidation degradation functional antimony-free polyester fiber has a breaking strength of 3.9 cN / dtex and an elongation at break of 22.3%.

[0041] Comparative Example 1

[0042] A method for manufacturing functional antimony-free polyester fiber is basically the same as that in Example 1, except that step (1) is omitted in Comparative Example 1, and titanium dioxide is directly added in step (2) instead of phosphate-modified thermal-oxidative-degradation-resistant functional nanopowder.

[0043] The prepared functional antimony-free polyester fiber has a breaking strength of 3.3 cN / dtex and an elongation at break of 10.8%.

[0044] Compared with Example 1, the breaking strength and breaking elongation of Comparative Example 1 are lower than those of Example 1. This is because the inorganic powder (titanium dioxide) in Comparative Example 1 is not well dispersed in the polyester matrix and agglomerates.

[0045] Comparative Example 2

[0046] A method for manufacturing anti-thermal oxidative degradation-resistant antimony-free polyester fiber is basically the same as that of Example 1, except that step (1) is omitted in Comparative Example 2, and triethyl phosphate is directly added in step (2) to replace the phosphate-modified anti-thermal oxidative degradation functional nanopowder.

[0047] Compared with Example 1, the initial decomposition temperature of the product of step (3) of Comparative Example 2 was reduced by 123°C, and the maximum thermal weight loss temperature was reduced by 8.7°C, both of which were lower than those of Example 1. This is because the small molecules of triethyl phosphate migrated and failed to achieve a good anti-thermal oxidative degradation effect.

[0048] Example 2

[0049] A method for producing a functional antimony-free polyester fiber resistant to thermal oxidation degradation, comprising the following steps:

[0050] (1) Preparation of phosphate-modified functional nanopowders resistant to thermal oxidation degradation;

[0051] An inorganic powder (zinc oxide) having an average particle size of 0.5 μm is dispersed in a solvent (anhydrous ethanol), and then a phosphate ester small molecule (phosphoric acid) having a thermal oxidative degradation resistance function is added thereto at 60° C. The pH value of the system is adjusted to 4. The mixture is kept warm, cooled, refluxed, and stirred for 40 minutes before being cooled to room temperature. The mixture is then filtered, washed (three times with anhydrous ethanol and three times with deionized water), and dried (110° C. for 10 hours) to obtain a phosphate-modified nanopowder having a thermal oxidative degradation resistance function. The content of the inorganic powder in the system is 1.8 wt %, and the content of the phosphate ester small molecule having a thermal oxidative degradation resistance function is 2 wt %.

[0052] The prepared phosphate-modified nanopowder with thermal-oxidative degradation resistance is an inorganic powder with phosphate-type small molecules deposited or coated on the surface, which has thermal-oxidative degradation resistance. The phosphate-type small molecules and the inorganic powder are bonded by van der Waals forces, hydrogen bonds or covalent bonds.

[0053] (2) Preparation of composite nanoagents resistant to thermal and oxidative degradation;

[0054] The phosphate modified anti-thermal oxidation degradation functional nano powder prepared in step (1) and polyethylene wax were stirred in a closed mixer at a temperature of 62° C. for 58 minutes to prepare an anti-thermal oxidation degradation composite nano agent in a weight ratio of 6.5:2;

[0055] (3) Preparation of functional antimony-free polyester;

[0056] The anti-thermal oxidative degradation composite nano-agent prepared in step (2), sodium hexametaphosphate and ethylene glycol are mixed in a weight ratio of 5:0.2:4, and ultrasonically dispersed at a temperature of 53° C. for 2 h to obtain functionalized ethylene glycol. When the esterification rate of polyethylene terephthalate polymerization reaches 86% (the catalyst used in the polymerization of polyethylene terephthalate is a titanium-based catalyst), the functionalized ethylene glycol is added thereto, and esterification reaction and polycondensation reaction are continued to obtain a functional antimony-free polyester, wherein the weight ratio of functionalized ethylene glycol to terephthalic acid is 35:65;

[0057] Compared with the control sample (the only difference between the control sample and the functional antimony-free polyester is that it does not contain phosphate-modified anti-thermal oxidation degradation functional nanopowder), the initial decomposition temperature of the prepared functional antimony-free polyester increased by 14°C and the maximum thermal weight loss temperature increased by 10°C.

[0058] (4) Preparation of anti-thermal oxidative degradation functional antimony-free polyester fiber;

[0059] Functional antimony-free polyester and antimony-free polyester (polyester produced using a titanium-based catalyst) are mixed to obtain a mixture, which is then melt-spun into a composite fiber to produce a functional antimony-free polyester fiber resistant to thermal oxidation degradation, wherein the content of the phosphate-modified anti-thermal oxidation degradation functional nanopowder in the functional antimony-free polyester fiber is 1.8 wt%.

[0060] The prepared anti-thermal oxidation degradation functional antimony-free polyester fiber has a breaking strength of 3.8 cN / dtex and an elongation at break of 25.2%.

[0061] Example 3

[0062] A method for producing a functional antimony-free polyester fiber resistant to thermal oxidation degradation, comprising the following steps:

[0063] (1) Preparation of phosphate-modified functional nanopowders resistant to thermal oxidation degradation;

[0064] An inorganic powder (cuprous oxide) having an average particle size of 0.6 μm is dispersed in a solvent (anhydrous ethanol), and a phosphate ester small molecule having a thermal oxidative degradation resistance function (triphenyl phosphate) is added thereto at 70° C. The pH value of the system is adjusted to 4. The mixture is kept warm, cooled, refluxed, and stirred for 50 minutes before being cooled to room temperature. The mixture is then filtered, washed (four times with anhydrous ethanol and four times with deionized water), and dried (110° C. for 11 hours) to obtain a phosphate-modified nanopowder having a thermal oxidative degradation resistance function. The content of the inorganic powder in the system is 2% by weight, and the content of the phosphate ester small molecule having a thermal oxidative degradation resistance function is 3% by weight.

[0065] The prepared phosphate-modified nanopowder with thermal-oxidative degradation resistance is an inorganic powder with phosphate-type small molecules deposited or coated on the surface, which has thermal-oxidative degradation resistance. The phosphate-type small molecules and the inorganic powder are bonded by van der Waals forces, hydrogen bonds or covalent bonds.

[0066] (2) Preparation of composite nanoagents resistant to thermal and oxidative degradation;

[0067] The phosphate modified anti-thermal oxidation degradation functional nano powder prepared in step (1) and polyethylene wax were stirred in a closed mixer at a temperature of 63° C. for 55 minutes to prepare an anti-thermal oxidation degradation composite nano agent in a weight ratio of 7:1.5;

[0068] (3) Preparation of functional antimony-free polyester;

[0069] The anti-thermal oxidative degradation composite nano-agent prepared in step (2), sodium hexametaphosphate and ethylene glycol were mixed in a weight ratio of 6:0.3:5, and ultrasonically dispersed at a temperature of 57° C. for 2 h to obtain functionalized ethylene glycol. When the esterification rate of polyethylene terephthalate polymerization reached 87% (the catalyst used in the polymerization of polyethylene terephthalate was a titanium-based catalyst), the functionalized ethylene glycol was added thereto, and esterification reaction and polycondensation reaction were continued to obtain a functional antimony-free polyester, wherein the weight ratio of functionalized ethylene glycol to terephthalic acid was 35:65;

[0070] Compared with the control sample (the only difference between the control sample and the functional antimony-free polyester is that it does not contain phosphate-modified anti-thermal oxidation degradation functional nanopowder), the initial decomposition temperature of the prepared functional antimony-free polyester increased by 14°C and the maximum thermal weight loss temperature increased by 11°C.

[0071] (4) Preparation of anti-thermal oxidative degradation functional antimony-free polyester fiber;

[0072] Functional antimony-free polyester and antimony-free polyester (polyester produced using a titanium-based catalyst) are mixed to obtain a mixture, which is then melt-spun into a composite fiber to produce a functional antimony-free polyester fiber resistant to thermal oxidation degradation, wherein the content of the phosphate-modified anti-thermal oxidation degradation functional nanopowder in the functional antimony-free polyester fiber is 2 wt%.

[0073] The prepared anti-thermal oxidation degradation functional antimony-free polyester fiber has a breaking strength of 3.7 cN / dtex and an elongation at break of 26.3%.

[0074] Example 4

[0075] A method for producing a functional antimony-free polyester fiber resistant to thermal oxidation degradation, comprising the following steps:

[0076] (1) Preparation of phosphate-modified functional nanopowders resistant to thermal oxidation degradation;

[0077] An inorganic powder (ferric oxide) having an average particle size of 0.7 μm is dispersed in a solvent (anhydrous ethanol), and a phosphate ester small molecule (trimethyl phosphate) having a thermal oxidative degradation resistance function is added thereto at 80° C. The pH value of the system is adjusted to 5. The mixture is kept warm, cooled, refluxed, and stirred for 60 minutes before being cooled to room temperature. The mixture is then filtered, washed (five times with anhydrous ethanol and five times with deionized water), and dried (110° C. for 11 hours) to obtain a phosphate-modified thermal oxidative degradation resistance nanopowder. The content of the inorganic powder in the system is 2.2 wt %, and the content of the phosphate ester small molecule having a thermal oxidative degradation resistance function is 4 wt %.

[0078] The prepared phosphate-modified nanopowder with thermal-oxidative degradation resistance is an inorganic powder with phosphate-type small molecules deposited or coated on the surface, which has thermal-oxidative degradation resistance. The phosphate-type small molecules and the inorganic powder are bonded by van der Waals forces, hydrogen bonds or covalent bonds.

[0079] (2) Preparation of composite nanoagents resistant to thermal and oxidative degradation;

[0080] The phosphate modified anti-thermal oxidation degradation functional nano powder prepared in step (1) and polyethylene wax were reacted in a closed mixer at a temperature of 65° C. with stirring for 53 minutes to prepare an anti-thermal oxidation degradation composite nano agent in a weight ratio of 7:2;

[0081] (3) Preparation of functional antimony-free polyester;

[0082] The anti-thermal oxidative degradation composite nano-agent prepared in step (2), sodium hexametaphosphate and ethylene glycol are mixed in a weight ratio of 8:0.5:5, and ultrasonically dispersed at a temperature of 60° C. for 3 h to obtain functionalized ethylene glycol. When the esterification rate of polyethylene terephthalate polymerization reaches 90% (the catalyst used in the polymerization of polyethylene terephthalate is a titanium-based catalyst), the functionalized ethylene glycol is added thereto, and esterification reaction and polycondensation reaction are continued to obtain a functional antimony-free polyester, wherein the weight ratio of functionalized ethylene glycol to terephthalic acid is 35:65;

[0083] Compared with the control sample (the only difference between the control sample and the functional antimony-free polyester is that it does not contain phosphate-modified anti-thermal oxidation degradation functional nanopowder), the initial decomposition temperature of the prepared functional antimony-free polyester increased by 14°C and the maximum thermal weight loss temperature increased by 12°C.

[0084] (4) Preparation of anti-thermal oxidative degradation functional antimony-free polyester fiber;

[0085] Functional antimony-free polyester and antimony-free polyester (polyester produced using a titanium-based catalyst) are mixed to obtain a mixture, which is then melt-spun into a composite fiber to produce a functional antimony-free polyester fiber resistant to thermal oxidation degradation, wherein the content of the phosphate-modified anti-thermal oxidation degradation functional nanopowder in the functional antimony-free polyester fiber resistant to thermal oxidation degradation is 2.2 wt%.

[0086] The prepared anti-thermal oxidation degradation functional antimony-free polyester fiber has a breaking strength of 3.6 cN / dtex and an elongation at break of 26.2%.

[0087] Example 5

[0088] A method for producing a functional antimony-free polyester fiber resistant to thermal oxidation degradation, comprising the following steps:

[0089] (1) Preparation of phosphate-modified functional nanopowders resistant to thermal oxidation degradation;

[0090] An inorganic powder (silicon dioxide) having an average particle size of 0.8 μm is dispersed in a solvent (anhydrous ethanol), and a phosphate ester small molecule having a thermal oxidative degradation resistance function (triphenyl phosphite) is added thereto at 90° C. The pH value of the system is adjusted to 5. The mixture is kept warm, cooled, refluxed, and stirred for 70 minutes before being cooled to room temperature. The mixture is then filtered, washed (twice with anhydrous ethanol and twice with deionized water), and dried (110° C. for 12 hours) to obtain a phosphate-modified nanopowder having a thermal oxidative degradation resistance function. The content of the inorganic powder in the system is 2.4% by weight, and the content of the phosphate ester small molecule having a thermal oxidative degradation resistance function is 5% by weight.

[0091] The prepared phosphate-modified nanopowder with thermal-oxidative degradation resistance is an inorganic powder with phosphate-type small molecules deposited or coated on the surface, which has thermal-oxidative degradation resistance. The phosphate-type small molecules and the inorganic powder are bonded by van der Waals forces, hydrogen bonds or covalent bonds.

[0092] (2) Preparation of composite nanoagents resistant to thermal and oxidative degradation;

[0093] The phosphate modified anti-thermal oxidation degradation functional nano powder prepared in step (1) and polyethylene wax were stirred in a closed mixer at a temperature of 67° C. for 50 minutes to prepare an anti-thermal oxidation degradation composite nano agent in a weight ratio of 8:1.5;

[0094] (3) Preparation of functional antimony-free polyester;

[0095] The functional antimony-free polyester is prepared by melt-blending the anti-thermal oxidation degradation composite nano-agent and antimony-free polyester (polyester prepared by using a titanium-based catalyst) in a weight ratio of 20:80;

[0096] Compared with the control sample (the only difference between the control sample and the functional antimony-free polyester is that it does not contain phosphate-modified anti-thermal oxidation degradation functional nanopowder), the initial decomposition temperature of the prepared functional antimony-free polyester increased by 15°C and the maximum thermal weight loss temperature increased by 11°C.

[0097] (4) Preparation of anti-thermal oxidative degradation functional antimony-free polyester fiber;

[0098] Functional antimony-free polyester and antimony-free polyester (polyester produced using a titanium-based catalyst) are mixed to obtain a mixture, which is then melt-spun into a composite fiber to produce a functional antimony-free polyester fiber resistant to thermal oxidation degradation, wherein the content of the phosphate-modified anti-thermal oxidation degradation functional nanopowder in the functional antimony-free polyester fiber is 2.4 wt%.

[0099] The prepared anti-thermal oxidation degradation functional antimony-free polyester fiber has a breaking strength of 3.6 cN / dtex and an elongation at break of 25.6%.

[0100] Example 6

[0101] A method for producing a functional antimony-free polyester fiber resistant to thermal oxidation degradation, comprising the following steps:

[0102] (1) Preparation of phosphate-modified functional nanopowders resistant to thermal oxidation degradation;

[0103] An inorganic powder (titanium dioxide) having an average particle size of 0.45 μm was dispersed in a solvent (anhydrous ethanol), and a phosphate ester small molecule having a thermal oxidative degradation resistance function (triphenyl phosphite) was added thereto at a temperature of 55° C. The pH value of the system was adjusted to 5, and the mixture was kept warm, cooled, refluxed, and stirred for 80 minutes before being cooled to room temperature. The mixture was then filtered, washed (three times with anhydrous ethanol and three times with deionized water), and dried (110° C. for 12 hours) to obtain a phosphate-modified nanopowder having a thermal oxidative degradation resistance function. The content of the inorganic powder in the system was 3% by weight, and the content of the phosphate ester small molecule having a thermal oxidative degradation resistance function was 6% by weight.

[0104] The prepared phosphate-modified nanopowder with thermal-oxidative degradation resistance is an inorganic powder with phosphate-type small molecules deposited or coated on the surface, which has thermal-oxidative degradation resistance. The phosphate-type small molecules and the inorganic powder are bonded by van der Waals forces, hydrogen bonds or covalent bonds.

[0105] (2) Preparation of composite nanoagents resistant to thermal and oxidative degradation;

[0106] The phosphate modified anti-thermal oxidation degradation functional nano powder prepared in step (1) and polyethylene wax were stirred in a closed mixer at a temperature of 69° C. for 47 minutes to prepare an anti-thermal oxidation degradation composite nano agent in a weight ratio of 9:2;

[0107] (3) Preparation of functional antimony-free polyester;

[0108] The functional antimony-free polyester is prepared by melt-blending the anti-thermal oxidative degradation composite nano-agent and antimony-free polyester (polyester prepared by using a titanium-based catalyst) in a weight ratio of 30:70;

[0109] Compared with the control sample (the only difference between the control sample and the functional antimony-free polyester is that it does not contain phosphate-modified anti-thermal oxidation degradation functional nanopowder), the initial decomposition temperature of the prepared functional antimony-free polyester increased by 15°C and the maximum thermal weight loss temperature increased by 10°C.

[0110] (4) Preparation of anti-thermal oxidative degradation functional antimony-free polyester fiber;

[0111] Functional antimony-free polyester and antimony-free polyester (polyester produced using a titanium-based catalyst) are mixed to obtain a mixture, which is then melt-spun into a composite fiber to produce a functional antimony-free polyester fiber resistant to thermal oxidation degradation, wherein the content of the phosphate-modified anti-thermal oxidation degradation functional nanopowder in the functional antimony-free polyester fiber resistant to thermal oxidation degradation is 3wt%.

[0112] The prepared anti-thermal oxidation degradation functional antimony-free polyester fiber has a breaking strength of 3.7 cN / dtex and an elongation at break of 22.4%.

[0113] Example 7

[0114] A method for producing a functional antimony-free polyester fiber resistant to thermal oxidation degradation, comprising the following steps:

[0115] (1) Preparation of phosphate-modified functional nanopowders resistant to thermal oxidation degradation;

[0116] An inorganic powder having an average particle size of 0.65 μm (a mixture of titanium dioxide and cuprous oxide in a mass ratio of 1:1) was dispersed in a solvent (anhydrous ethanol), and then a phosphate ester small molecule having a thermal oxidative degradation resistance function (a mixture of triethyl phosphate and phosphoric acid in a mass ratio of 1:1) was added thereto at 75° C. The pH value of the system was adjusted to 5. The mixture was kept warm, cooled, refluxed, and stirred for 90 minutes before being cooled to room temperature. The mixture was then filtered, washed (four times with anhydrous ethanol and four times with deionized water), and dried (110° C. for 12 hours) to obtain a phosphate-modified thermal oxidative degradation-resistant nanopowder. The content of the inorganic powder in the system was 3.5 wt %, and the content of the phosphate ester small molecule having a thermal oxidative degradation resistance function was 1.5 wt %.

[0117] The prepared phosphate-modified nanopowder with thermal-oxidative degradation resistance is an inorganic powder with phosphate-type small molecules deposited or coated on the surface, which has thermal-oxidative degradation resistance. The phosphate-type small molecules and the inorganic powder are bonded by van der Waals forces, hydrogen bonds or covalent bonds.

[0118] (2) Preparation of composite nanoagents resistant to thermal and oxidative degradation;

[0119] The phosphate modified anti-thermal oxidation degradation functional nano powder prepared in step (1) and polyethylene wax were reacted in a closed mixer at a temperature of 70° C. with stirring for 45 minutes to prepare an anti-thermal oxidation degradation composite nano agent in a weight ratio of 10:1.5;

[0120] (3) Preparation of functional antimony-free polyester;

[0121] The functional antimony-free polyester is prepared by melt-blending the anti-thermal oxidation degradation composite nano-agent and antimony-free polyester (polyester prepared by using a titanium-based catalyst) in a weight ratio of 40:60;

[0122] Compared with the control sample (the only difference between the control sample and the functional antimony-free polyester is that it does not contain phosphate-modified anti-thermal oxidation degradation functional nanopowder), the initial decomposition temperature of the prepared functional antimony-free polyester increased by 14°C and the maximum thermal weight loss temperature increased by 11°C.

[0123] (4) Preparation of anti-thermal oxidative degradation functional antimony-free polyester fiber;

[0124] Functional antimony-free polyester and antimony-free polyester (polyester produced using a titanium-based catalyst) are mixed to obtain a mixture, which is then melt-spun into a composite fiber to produce a functional antimony-free polyester fiber resistant to thermal oxidation degradation, wherein the content of the phosphate-modified anti-thermal oxidation degradation functional nanopowder in the functional antimony-free polyester fiber is 3.5wt%.

[0125] The prepared anti-thermal oxidation degradation functional antimony-free polyester fiber has a breaking strength of 3.65 cN / dtex and an elongation at break of 23.1%.

Claims

1. A method for producing anti-thermal oxidation degradation functional antimony-free polyester fiber, characterized in that: After introducing phosphate-modified anti-thermal oxidation degradation functional nanopowder into antimony-free polyester to obtain functional antimony-free polyester, spinning the anti-thermal oxidation degradation functional antimony-free polyester fiber using the anti-thermal oxidation degradation functional nanopowder as part or all of the raw material; The phosphate-modified nanopowder with thermal-oxidative-degradation resistance function is an inorganic powder with phosphate-type small molecules deposited or coated on the surface with thermal-oxidative-degradation resistance function. The phosphate-type small molecules are bonded to the inorganic powder through van der Waals force, hydrogen bond or covalent bond. The phosphate-type small molecules are phosphate-type molecules with a molecular weight of less than 500Da. The average particle size of the inorganic powder is 0.4-0.8μm. The phosphate ester small molecule having the function of resisting thermal oxidation degradation is one or more of triethyl phosphate, phosphoric acid, triphenyl phosphate, trimethyl phosphate and triphenyl phosphite; The inorganic powder is one or more of titanium dioxide, cuprous oxide, ferric oxide and silicon dioxide; The preparation process of the phosphate-modified nanometer powder with anti-thermal oxidation degradation function is as follows: after dispersing the inorganic powder in a solvent, adding the phosphate-type small molecules with anti-thermal oxidation degradation function therein at a temperature of 50-90° C., adjusting the pH value of the system to 4-5, keeping the temperature, cooling, refluxing and stirring the reaction for 30-90 minutes, cooling to room temperature, and then filtering, washing and drying to obtain the phosphate-modified nanometer powder with anti-thermal oxidation degradation function; the content of the inorganic powder in the system is 1-5wt%, and the content of the phosphate-type small molecules with anti-thermal oxidation degradation function is 1-6wt%.

2. The method for producing a thermal-oxidative-degradation-resistant functional antimony-free polyester fiber according to claim 1, characterized in that: Before introduction, the phosphate modified anti-thermal oxidation degradation functional nano powder and polyethylene wax are reacted in a closed stirring reaction in a mixer at a temperature of 60-70° C. for 45-60 minutes in a weight ratio of 6-10:1.5-2 to obtain an anti-thermal oxidation degradation composite nano agent.

3. The method for producing a functional antimony-free polyester fiber resistant to thermal oxidation degradation according to claim 2, characterized in that: The introduction process is as follows: firstly, the anti-thermal oxidation degradation composite nano-agent, sodium hexametaphosphate and ethylene glycol are mixed in a weight ratio of 4-8:0.1-0.5:3-5, and then ultrasonically dispersed for 2-3 hours at a temperature of 50-60°C to obtain functionalized ethylene glycol, and then when the polymerization esterification rate of polyethylene terephthalate reaches 85-90%, the functionalized ethylene glycol is added thereto, and esterification reaction and polycondensation reaction are continued to obtain functional antimony-free polyester, wherein the weight ratio of the functionalized ethylene glycol to terephthalic acid is 35:65, and terephthalic acid is one of the reaction raw materials of polyethylene terephthalate.

4. The method for producing a thermal-oxidative-degradation-resistant functional antimony-free polyester fiber according to claim 2, characterized in that: The introduction process is: melt-blending the anti-thermal oxidation degradation composite nano-agent and the antimony-free polyester in a weight ratio of 20:80 to 40:60 to obtain the functional antimony-free polyester.

5. The method for producing a functional antimony-free polyester fiber resistant to thermal oxidation degradation according to claim 3 or 4, characterized in that: The spinning process is: functional antimony-free polyester and antimony-free polyester are mixed to obtain a mixture, and then melt-spinning is performed to obtain a functional antimony-free polyester fiber resistant to thermal oxidation degradation, wherein the content of phosphate-modified anti-thermal oxidation degradation functional nanopowder in the functional antimony-free polyester fiber resistant to thermal oxidation degradation is 1.5-3.5wt%.

Citation Information

Patent Citations

  • Ageing-resistant high-strength nylon filament suitable for outdoor use, and preparation method thereof

    CN101545152A

  • Oiling roller for chemical fiber yarn production

    CN112281225A

  • Uvioresistant poly butylene succinate fiber

    CN101671860A

  • Preparation method of functional polyester

    CN103788349A

  • 190 DEG C-grade PET (Polyethylene Terephthalate) insulating film and preparation method thereof

    CN106317792A